Exosomes: Basic Biology and Technological Advancements Suggesting Their Potential as Ischemic Heart Disease Therapeutics - Shanmuganathan, Mayooran; Vughs, Jeff; Noseda, Michela; Emanueli, Costanza (Frontiers in Physiology, 2018)
Exosomes are small nano-sized vesicles that deliver biologically active RNA molecules and proteins to recipient cells through binding, fusion or endocytosis. There is emerging evidence that endogenous exosomes released by cardiovascular cells and progenitor cells impact cell survival and proliferation, thus regulating angiogenesis, cardiac protection and repair. These cardioprotective and regenerative traits have the potential to translate in to novel therapeutic options for post-ischaemic cardiac regeneration, thus potentially delaying the progression to ischaemic heart failure. Cellular stressors influence exosomes’ secretion and the molecular composition of the exosome cargo, thus impacting on the above processes. Evidences are emerging that loading of proteins and RNAs in the exosomes cargos can be manipulated. Similarly, manipulation of exosomes surface proteins’ expression to target exosomes to specific cells and tissues is doable. In addition, nature-inspired synthetic exosomes can be assembled to deliver specific clues to the recipient cells, including proliferative and differentiation stimuli, or shed paracrine signals enabling to reconstructing the heart homeostatic micro-environment. This review will describe exosome biogenesis and emerging evidence of exosome-mediated regenerative cell-to-cell communications and will conclude discussing possibilities of using exosomes to treat ischemic heart disease.